Final Year Project Allocation System Techniques: A Systematic Literature Review - Nik Intan Syahiddatul Ilani, Jailani; Mubarak-Ali, Al-Fahim; Syahrulanuar, Ngah (IEEE, 2022)
Undergraduate students require to undertake the Final Year Project (FYP) for the completion of their studies. The allocation of FYP can be fundamental for students to be allocated to the project based on their interest with supervisors that expertise in their project field. However, the usual practice for the FYP allocation process is done manually by the FYP Coordinator. In this paper, few studies have been made on existing FYP allocation systems. Besides, we also focus on allocation techniques to provide the best decision which satisfied both lecturer and student preferences and lesser the workload of the FYP Coordinator. The existing FYP System which includes subject allocation and implemented the allocation techniques were highlighted and presented. The efficiency of the system is identified through the highest project allocation accuracy and shows the best FYP system and allocation technique. Therefore, this paper focused on a systematic literature review (SLR) from a previous study regarding the existing Final Year Project Allocation System and allocation techniques.